THE GUIDELINES FOR STRENGTHENING VISIONARY LEADERSHIP OF SCHOOL ADMINISTRATORS IN THE NAKHON SAWAN PRIMARY EDUCATIONAL SERVICE AREA 1 ACCORDING TO PĀPAṆIKA-DHAMMA - Ampas, Aunchuree; Gesthong, Thanee; Thuenchang, Worrakrit (Journal of Educational Review Faculty of Education in MCU, 2024)
This research aims to 1) study the visionary leadership of school administrators and 2) find ways to enhance visionary leadership of school administrators according to the Pāpaṇika-dhamma principle (Qualities of a successful businessman). It is a mixed-method research. The quantitative research used a questionnaire with a sample of 292 people. The data were analyzed using research statistics, including frequency, percentage, mean, and standard deviation. The qualitative research used interviews with 9 key informants. The results of the research found that 1) the visionary leadership of school administrators in the Nakhon Sawan Primary Educational Service Area 1 overall had the highest opinions. When considering each aspect, the opinions were at the highest levels in all 4 aspects: being a good role model, disseminating vision, practicing vision, and creating vision, respectively. 2) The guidelines for enhancing visionary leadership of school administrators according to the Pāpaṇika-dhamma principle consisted of (1) Creating vision, supporting school administrators in systematically compiling information to be used to determine the vision so that administrators had the knowledge and ability to manage and use modern digital technology devices. (2) Disseminating vision, setting a plan for school administrators to hold meetings with parents of students to exchange opinions with teachers and parents of students and disseminate the vision, learning techniques through various communication channels. (3) Vision practice, promoting educational institution administrators to have a process for planning operations according to the vision, in supervising, evaluating, following up and reporting the results of operations according to the vision using digital technology. (4) Being a role model, promoting educational institution administrators to create networks for developing morality and ethics, promoting administrators to use digital technology in evaluating, developing morality, ethics, morality, ethics and announcing the honors of good administrators.